ISLAMIC CORPORATE SOCIAL RESPONBILITY PENGARUHNYA PADA PROFITABILITAS KEUANGAN DI JAKARTA ISLAMIC INDEX/JII - Lely Ana Ferawati Ekaningsih; Istiqomah, Istiqomah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
The study aims to analyze whether there is an influence between Islamic Corporate social responsibility (X) on the financial profitability (Y) of companies in the Jakarta Islamic Index. This research uses quantitative methods. The data used is secondary data in the form of an annual report. The data analysis technique used the data normality test and then used the regression model. The research population is a company registered on the Jakarta Islamic Index totaling 30. The sample is manufacturing at JII, totaling 10 for 3 years, from 2016-2018. The results of the study show that there is an influence between Islamic Corporate Social Responsibility (X) on the financial profitability (Y) of companies in JII. This shows that disclosure and reporting of corporate social responsibility activities carried out by companies in accordance with Islamic law can increase company profitability